Silica gel composite adsorption separation material and preparation method thereof
Patent Information
- Application Number
- CN202610556955.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-04-24
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2046-04-24
AI Technical Summary
该新型硅胶复合物吸附分离材料可用于吸附吸附气相和液相中的疏水性物质,但是其吸附容量仍有待提高
[0016]由于采用以上技术方案,本发明的有益效果包括:
Smart Images

Figure CN122321836B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of adsorption separation technology, specifically to a silica gel composite adsorption separation material and its preparation method. Background Technology
[0002] With rapid industrialization, the massive emissions of volatile organic compounds (VOCs) and greenhouse gases have led to severe air pollution problems. Adsorption separation has become the preferred treatment technology due to its high efficiency and low cost. Currently, while traditional porous silica gel adsorbents offer advantages such as low cost, high mechanical strength, and good hydrodynamic properties, their surfaces are rich in polar hydrophilic hydroxyl groups, resulting in poor selectivity for non-polar pollutants. They are particularly prone to significant deactivation due to competitive adsorption by water molecules in high humidity environments. On the other hand, emerging metal-organic frameworks (MOFs, such as ZIF-8) materials, while possessing ultra-high specific surface area and excellent hydrophobicity, suffer from limitations in engineering applications due to difficulties in powder forming and large bed pressure drops. Existing technologies often attempt to construct composite materials by physically coating MOFs onto silica gel or using conventional aminosilane coupling agents (such as APTES). However, the bonding forces at such heterogeneous interfaces are extremely weak, lacking a basis for homologous growth. When faced with long-term airflow scouring of industrial waste gas and frequent high-temperature thermal desorption and regeneration cycles, the MOF active coating is prone to large-area powdering and peeling.
[0003] Chinese invention patent CN101804321A discloses a novel silica gel composite adsorption and separation material and its preparation. The novel silica gel composite adsorption and separation material contains 30-98 wt% silica gel and 2-70 wt% mesoporous silica material. The preparation method includes the following steps: mixing the raw powder of mesoporous silica material with an alkaline silicate solution, then instantaneously mixing the mixture with an inorganic acid to obtain a silica gel mesoporous composite material. The template agent is then removed, and the template-removed silica gel mesoporous composite material is hydrophobically modified with a coupling agent to obtain the novel silica gel composite adsorption and separation material. This novel silica gel composite adsorption and separation material can be used to adsorb hydrophobic substances in the gas and liquid phases, but its adsorption capacity still needs improvement.
[0004] Therefore, developing a novel composite adsorption and separation material with both high adsorption capacity and ultra-long cycle life is of profound significance for improving the overall effectiveness of air pollution control. Summary of the Invention
[0005] To address the shortcomings of existing technologies, the purpose of this invention is to provide a silica gel composite adsorption and separation material and its preparation method.
[0006] A method for preparing a silica gel composite adsorption and separation material includes the following steps: (1) Add macroporous silica gel to dilute nitric acid solution, heat and stir, wash with water until neutral, and then dry to obtain activated silica gel; (2) Disperse activated silica gel in anhydrous toluene, add modified silane coupling agent, reflux reaction, wash and dry to obtain modified silica gel; (3) The modified silica gel was immersed in zinc salt solution, 2-methylimidazole solution was added dropwise, the reaction was stirred, filtered, washed and vacuum activated to obtain silica gel composite adsorption and separation material; The structural formula of the modified silane coupling agent is as follows:
[0007] In step (1), 5-15 mL of dilute nitric acid solution is added to every 1 g of the macroporous silica gel.
[0008] In step (1), the heating and stirring treatment is carried out at a temperature of 80-100℃ for 4-8 hours.
[0009] In step (2), the mass ratio of activated silica gel to modified silane coupling agent is 1:(0.1-0.5).
[0010] In step (2), the reflux reaction is carried out under inert gas protection, the reaction temperature is 90-100℃, and the reaction time is 12-24h.
[0011] In step (3), the zinc salt is zinc nitrate.
[0012] In step (3), the concentration of the zinc salt solution is 0.1-0.25 mol / L, and the solvent of the zinc salt solution is one of methanol and ethanol; the concentration of the 2-methylimidazole solution is 2.0-2.5 mol / L, and the solvent of the 2-methylimidazole solution is one of methanol and ethanol.
[0013] In step (3), 25-45 mL of the zinc salt solution and 5-10 mL of the 2-methylimidazole solution are added to 1 g of the modified silica gel.
[0014] In step (3), the vacuum activation temperature is 80-100℃ and the time is 12-24h.
[0015] A silica gel composite adsorption and separation material is prepared by the above method.
[0016] Due to the adoption of the above technical solutions, the beneficial effects of the present invention include: The novel silica gel composite adsorption and separation material prepared by this invention has high penetration adsorption capacity and excellent ultra-long cycle life. Attached Figure Description
[0017] Figure 1The 1H NMR spectrum of the modified silane coupling agent prepared in Example 1 is shown.
[0018] Figure 2 The high-resolution mass spectrum of the modified silane coupling agent prepared in Example 1 is shown.
[0019] Figure 3 This is a transmission electron microscope (TEM) image of the novel silica gel composite adsorption and separation material prepared in Example 3. Detailed Implementation
[0020] Example 1: Preparation of Modified Silane Coupling Agent S1: Under nitrogen protection, 150 ml of acetonitrile and 0.103 mol of cyanuric chloride were stirred and mixed. Then, 250 ml of an acetonitrile solution containing 0.1 mol of 1-amino-3,6,9,12-tetraoxapentadecan-15-acid and 0.2 mol of N,N-diisopropylethylamine was slowly added dropwise over 40 min. The reaction was carried out at 0℃ for 6 h, and then rotary evaporated at 60℃ to constant weight. 400 ml of dichloromethane was added to dissolve the residue, and the solution was transferred to a separatory funnel. The solution was washed successively with 300 ml of cold 0.2 M dilute hydrochloric acid and 200 ml of saturated saline solution. After standing and separating the layers, the lower organic phase was collected, dried with 40 g of anhydrous sodium sulfate, filtered, and the filtrate was rotary evaporated at 30℃ to constant weight to obtain intermediate A. The reaction equation is shown below:
[0021] Its 1H NMR data are as follows: 1 H NMR (400 MHz, DMSO- d 6 ) δ 11.40 (s, 1H), 7.03 (t,J = 4.8Hz, 1H), 3.79 – 3.50 (m, 18H), 2.46 (t, J = 6.4 Hz, 2H); HRMS (m / z): 413.0919[M+H] + .
[0022] S2: Under nitrogen protection, 300 ml of tetrahydrofuran and 0.1 mol of intermediate A were stirred and mixed. Then, 250 ml of a tetrahydrofuran solution containing 0.105 mol of 6-aminomethylquinoline and 0.2 mol of N,N-diisopropylethylamine was slowly added dropwise over 50 min. The reaction was carried out at 40 °C for 8 h. After the reaction was complete, the mixture was rotary evaporated at 40 °C to constant weight. 400 ml of dichloromethane was added to dissolve the mixture, and the solution was transferred to a separatory funnel. The solution was washed successively with 300 ml of cold 0.2 M dilute hydrochloric acid and 200 ml of saturated saline solution. The organic phase was dried over 40 g of anhydrous sodium sulfate, filtered, and the filtrate was rotary evaporated at 30 °C to constant weight. The filtrate was then dried under vacuum at 60 °C for 8 h to obtain intermediate B. The reaction equation is shown below:
[0023]
[0024] Its 1H NMR data are as follows: 1 H NMR (400 MHz, DMSO- d 6 ) δ 11.41 (s, 1H), 8.80 (dd, J = 4.2, 1.7 Hz, 1H), 8.12 (dddd, J = 8.3, 3.1, 2.7, 1.5 Hz, 1H), 7.93 –7.86 (m, 2H), 7.57 – 7.42 (m, HRMS (m / z):535.1998[M+H] + .
[0025] S3: Under nitrogen protection, 300 ml of anhydrous toluene and 0.1 mol of intermediate B were stirred and mixed thoroughly. Then, 350 ml of anhydrous tetrahydrofuran solution containing 0.108 mol of 3-aminopropyltriethoxysilane and 0.2 mol of N,N-diisopropylethylamine was slowly added dropwise over 60 min. After the addition was complete, the mixture was heated to 80 °C and reacted for 20 h. After the reaction was completed, the mixture was cooled to room temperature and rotary evaporated at 90 °C to constant weight. 300 ml of cold anhydrous ethyl acetate was added and stirred to dissolve the filtrate. The filtrate was then collected and rotary evaporated at 40 °C to constant weight to obtain the modified silane coupling agent. The reaction equation is shown below:
[0026]
[0027] Its proton nuclear magnetic resonance spectrum is as follows Figure 1 As shown, its 1H NMR spectrum data are as follows: 1 H NMR (400 MHz, Chloroform- d) δ 10.60 (s, 1H), 8.81 (dd, J = 4.1, 1.7 Hz, 1H), 8.10 (dddd, J= 8.3, 3.2, 2.5, 1.6 Hz, 1H), 7.91 – 7.85 (m, 2H), 7.53 – 7.41 (m, 2H), 7.17(t, J = 5.2 Hz, 1H), 6.26 – 6.20 (m, 1H), 5.94 (t, J = 4.2 Hz, 1H), 4.82 (dt,J = 5.2, 1.9 Hz, 2H), 3.82 (q, J = 7.5 Hz, 6H), 3.77 – 3.61 (m, 18H), 3.52 (td, J = 8.3, 4.2 Hz, 2H), 2.51 (t, J = 6.4 Hz, 2H), 1.92 – 1.81 (m, 2H), 1.21 (t, J = 7.5 Hz, 9H), 0.75 (t, J = 8.9 Hz, 2H); its high-resolution mass spectrum is as follows: Figure 2 As shown, HRMS (m / z): 720.3672 [M+H] + .
[0028] Example 2: Preparation of a novel silica gel composite adsorption and separation material (1) Weigh 10g of macroporous silica gel and place it in a round-bottom flask. Add 50ml of 10wt% dilute nitric acid solution, heat to 80℃, and stir for 8h. After the reaction is complete, filter the filter cake and wash it with deionized water until the pH of the eluent is neutral. Wash it three times with anhydrous ethanol (50ml each time) and dry it in an 80℃ vacuum drying oven for 12h to obtain activated silica gel. (2) Under nitrogen protection, 10g of the above activated silica gel was dispersed in 100ml of anhydrous toluene and ultrasonically dispersed for 15min. 20ml of anhydrous toluene solution containing 1g of modified silane coupling agent (prepared in Example 1) was slowly added dropwise. After the addition was completed in 10min, the mixture was stirred and mixed. The temperature was raised to 90℃ and the reaction was carried out for 24h. After the reaction was completed, the mixture was cooled to room temperature and filtered. The filter cake was washed three times with anhydrous toluene (50ml each time) and three times with anhydrous ethanol (50ml each time). It was then placed in a vacuum drying oven at 60℃ and dried for 12h to obtain modified silica gel. (3) 10g of modified silica gel was immersed in 250ml of 0.1mol / L zinc nitrate methanol solution and allowed to stand at room temperature for 1h. Then, 50ml of 2.0mol / L 2-methylimidazolium methanol solution was slowly added dropwise. After the addition was completed in 20min, the mixture was stirred and reacted at room temperature for 12h. The mixture was filtered, washed 5 times with methanol (50ml each time), and placed in a vacuum drying oven. It was then vacuum activated at 80℃ for 24h to obtain a novel silica gel composite adsorption and separation material.
[0029] Example 3: Preparation of a novel silica gel composite adsorption and separation material (1) Weigh 10g of macroporous silica gel and place it in a round-bottom flask. Add 100ml of 10wt% dilute nitric acid solution, heat to 90℃, and stir for 6h. After the reaction is complete, filter the filter cake and wash it with deionized water until the pH of the eluent is neutral. Wash it three times with anhydrous ethanol (50ml each time) and dry it in a vacuum drying oven at 80℃ for 12h to obtain activated silica gel. (2) Under nitrogen protection, 10g of the above activated silica gel was dispersed in 100ml of anhydrous toluene and ultrasonically dispersed for 15min. 20ml of anhydrous toluene solution containing 3g of modified silane coupling agent (prepared in Example 1) was slowly added dropwise. After the addition was completed in 10min, the mixture was stirred and mixed. The temperature was raised to 95℃ and the reaction was carried out for 18h. After the reaction was completed, the mixture was cooled to room temperature and filtered. The filter cake was washed three times with anhydrous toluene (50ml each time) and three times with anhydrous ethanol (50ml each time). It was then placed in a vacuum drying oven at 60℃ and dried for 12h to obtain modified silica gel. (3) 10g of modified silica gel was immersed in 350ml of 0.15mol / L zinc nitrate ethanol solution and allowed to stand at room temperature for 1h. Then, 80ml of 2.25mol / L 2-methylimidazolium ethanol solution was slowly added dropwise. After the addition was completed in 20min, the mixture was stirred and reacted at room temperature for 12h. The mixture was filtered, washed 5 times with methanol (50ml each time), and placed in a vacuum drying oven. It was then vacuum activated at 90℃ for 18h to obtain the novel silica gel composite adsorption and separation material.
[0030] Figure 3 The image shows a TEM image of the adsorption and separation material. The light-colored, interwoven, and irregularly sponge-like continuous phase in the image is a macroporous silica skeleton. On the surface and in the pores of the silica skeleton, a large number of dark-colored particles with clear polyhedrals are densely and uniformly attached. These polyhedral particles are ZIF-8 nanoparticles grown in situ.
[0031] Example 4: Preparation of a novel silica gel composite adsorption and separation material (1) Weigh 10g of macroporous silica gel and place it in a round-bottom flask. Add 150ml of 10wt% dilute nitric acid solution, heat to 100℃, and stir for 4h. After the reaction is complete, filter the filter cake and wash it with deionized water until the pH of the eluent is neutral. Wash it three times with anhydrous ethanol (50ml each time) and dry it in an 80℃ vacuum drying oven for 12h to obtain activated silica gel. (2) Under nitrogen protection, 10g of the above activated silica gel was dispersed in 100ml of anhydrous toluene and ultrasonically dispersed for 15min. 20ml of anhydrous toluene solution containing 5g of modified silane coupling agent (prepared in Example 1) was slowly added dropwise. After the addition was completed in 10min, the mixture was stirred and mixed. The temperature was raised to 100℃ and the reaction was carried out for 12h. After the reaction was completed, the mixture was cooled to room temperature and filtered. The filter cake was washed three times with anhydrous toluene (50ml each time) and three times with anhydrous ethanol (50ml each time). It was then placed in a vacuum drying oven at 60℃ and dried for 12h to obtain modified silica gel. (3) 10g of modified silica gel was immersed in 450ml of 0.25mol / L zinc nitrate methanol solution and allowed to stand at room temperature for 1h. Then, 100ml of 2.5mol / L 2-methylimidazolium methanol solution was slowly added dropwise. After the addition was completed in 20min, the reaction was stirred at room temperature for 12h. The mixture was filtered, washed 5 times with methanol (50ml each time), and placed in a vacuum drying oven for vacuum activation at 100℃ for 12h to obtain a novel silica gel composite adsorption and separation material.
[0032] Comparative Example 1 The preparation method of the novel silica gel composite adsorption and separation material is basically the same as that in Example 3, except that the modified silane coupling agent is replaced with an equal weight of the modified silane coupling agent prepared by the following method: The preparation method of the modified silane coupling agent is basically the same as that in Example 1, except that the 1-amino-3,6,9,12-tetraoxapentadecan-15-acid in step S1 is replaced with an equimolar amount of 2-(2-(2-aminoethoxy)ethoxy)acetic acid.
[0033] Comparative Example 2 The preparation method of the novel silica gel composite adsorption and separation material is basically the same as that in Example 3, except that the modified silane coupling agent is replaced with an equal weight of the modified silane coupling agent prepared by the following method: The preparation method of the modified silane coupling agent is basically the same as that in Example 1, except that the 1-amino-3,6,9,12-tetraoxapentadecan-15-acid in step S1 is replaced with an equimolar amount of 15-aminopentadecanoic acid.
[0034] Comparative Example 3 The preparation method of the novel silica gel composite adsorption and separation material is basically the same as that in Example 3, except that the modified silane coupling agent is replaced with an equal weight of the modified silane coupling agent prepared by the following method: The preparation method of the modified silane coupling agent is basically the same as that in Example 1, except that 6-aminomethylquinoline in step S2 is replaced with an equimolar amount of 3-aminomethylpyridine.
[0035] Comparative Example 4 The preparation method of the novel silica gel composite adsorption and separation material is basically the same as that in Example 3, except that the modified silane coupling agent is replaced with an equal weight of the modified silane coupling agent prepared by the following method: The preparation method of the modified silane coupling agent is basically the same as that in Example 1, except that 3-aminopropyltriethoxysilane in step S3 is replaced with an equimolar amount of (3-aminopropyl)diethoxyethylsilane.
[0036] Comparative Example 5 The preparation method of the novel silica gel composite adsorption and separation material is basically the same as that in Example 3, except that the modified silane coupling agent is replaced with an equal weight of 3-aminopropyltriethoxysilane.
[0037] Comparative Example 6 The preparation method of the novel silica gel composite adsorption and separation material is as follows: (1) Under nitrogen protection, 10g of macroporous silica gel was dispersed in 100ml of anhydrous toluene and ultrasonically dispersed for 15min. 20ml of anhydrous toluene solution containing 3g of modified silane coupling agent (prepared in Example 1) was slowly added dropwise. After the addition was completed in 10min, the mixture was stirred and mixed. The temperature was raised to 95℃ and the reaction was carried out for 18h. After the reaction was completed, the mixture was cooled to room temperature and filtered. The filter cake was washed three times with anhydrous toluene (50ml each time) and three times with anhydrous ethanol (50ml each time). It was then placed in a vacuum drying oven at 60℃ and dried for 12h to obtain modified silica gel. (2) 10g of modified silica gel was immersed in 350ml of 0.15mol / L zinc nitrate ethanol solution and allowed to stand at room temperature for 1h. Then, 80ml of 2.25mol / L 2-methylimidazolium ethanol solution was slowly added dropwise. After the addition was completed in 20min, the mixture was stirred and reacted at room temperature for 12h. The mixture was filtered, washed 5 times with methanol (50ml each time), and placed in a vacuum drying oven. It was then activated under vacuum at 90℃ for 18h to obtain a novel silica gel composite adsorption and separation material.
[0038] Comparative Example 7 The preparation method of the novel silica gel composite adsorption and separation material is basically the same as that in Example 3, except that zinc nitrate is replaced with an equal weight of zinc acetate.
[0039] The macroporous silicone used in the embodiments and comparative examples of this application is Davisil® Grade 646.
[0040] The novel silica gel composite adsorption and separation materials prepared in the examples and comparative examples were tested for breakthrough adsorption capacity and long-term stability. The test results are shown in Table 1.
[0041] Breakthrough Adsorption Test: Accurately weigh 0.5g of the sample to be tested and uniformly fill it into a quartz glass adsorption tube with an inner diameter of 6mm. After filling, first purge with pure nitrogen and then heat at 150℃ for 2 hours to thoroughly remove the moisture and impurities adsorbed in the material pores. Then cool to 25℃ and hold at a constant temperature for testing. Introduce a toluene / nitrogen mixed standard gas with a concentration of 1000ppm, controlling the total gas flow rate at 50ml / min. Detection Method: The tail gas from the adsorption tube is connected to a gas chromatograph equipped with a flame ionization detector (FID) to monitor the toluene concentration in the tail gas in real time (denoted as C). The total inlet gas concentration is denoted as C0. Data Processing: When the tail gas concentration reaches 5% of the inlet gas concentration (C / C0=0.05), it is recorded as the breakthrough point; when the tail gas concentration reaches 95% of the inlet gas concentration (C / C0=0.95), it is considered adsorption saturation. The breakthrough adsorption capacity per gram of material is calculated by integrating the breakthrough curve; the calculation formula is as follows:
[0042]
[0043] q: The breakthrough adsorption capacity per unit mass of adsorbent, expressed in mg / g; Q: Volumetric flow rate of the mixed gas, in L / min; C0: Initial mass concentration of toluene in the intake air, in mg / L; W: Mass of the sample to be tested packed in the adsorption tube, in grams; t: Adsorption time, in minutes; t b Penetration time, in minutes, is the time point at which the exhaust gas concentration reaches 5% of the intake gas concentration (C / C0=0.05). C: Real-time mass concentration of toluene in the exhaust gas, in mg / L.
[0044] Long-term stability: Tested using a temperature-switching adsorption-desorption cycle method. The test steps are as follows:
[0045] (1) Adsorption stage: Toluene adsorption was carried out under the above dry test conditions until the material was completely saturated (C / C0=1.0), and the adsorption amount of the first cycle was recorded.
[0046] (2) Thermal desorption stage: switch to pure nitrogen purging (50 ml / min), and at the same time start the heating program to heat the bed to 150°C at a heating rate of 10°C / min. Maintain constant temperature desorption for 120 min to completely desorb toluene in the material pores.
[0047] (3) Cooling and circulation: After cooling to 25°C, the toluene mixture is reintroduced for the next adsorption.
[0048] (4) Repeat the above "adsorption-thermal desorption" process 20 times and record the adsorption amount in the 20th cycle.
[0049] The formula for calculating the cycle performance retention rate is: Performance retention rate after 20 cycles (%) = Adsorption amount in the 20th cycle / Adsorption amount in the first cycle × 100%.
[0050] Table 1 Performance Test Data of Adsorption Separation Materials Example 2 228 94.2 Example 3 245 96.5 Example 4 236 95.1 Comparative Example 1 203 90.3 Comparative Example 2 178 84.6 Comparative Example 3 187 87.5 Comparative Example 4 212 68.4 Comparative Example 5 134 54.2 Comparative Example 6 89 38.7 Comparative Example 7 221 93.9 As can be seen from the data in Examples 2-4 in Table 1, the novel silica gel composite adsorption and separation material prepared by the present invention has high penetration adsorption capacity and excellent ultra-long cycle life.
[0051] This invention utilizes the synergistic effect of surface chemical modification and in-situ MOF growth to prepare a supported silica composite adsorption and separation material with a hierarchical porous structure. In step (1), heat treatment with dilute nitric acid effectively removes impurities from the macroporous silica channels and fully hydroxylates its surface, exposing a high density of active silanol groups, providing ample reaction sites for subsequent chemical bonding. In step (2), the hydroxyl groups on the activated silica surface undergo a dehydration condensation reaction with triethoxysilane in the modified silane coupling agent, forming a robust Si-O-Si covalent network. Functional groups are introduced into the silica surface through covalent grafting, constructing a functionalized interface layer rich in coordinating active sites, serving as anchoring points for subsequent MOF crystal nucleation and growth. Simultaneously, the long, flexible PEG chains improve the solubility and dispersibility of the modified silane coupling agent, and their excellent spatial extensibility allows the terminal active groups to extend more flexibly to the silica channel surface, significantly improving the effective utilization rate of active sites. Step (3) involves introducing zinc nitrate and 2-methylimidazole to carry out a self-assembly and in-situ reaction, thereby growing zinc-based microporous MOF (i.e., ZIF-8) crystals with regular structures on the surface and in the pores of silica gel. During the in-situ growth stage, the nitrogen atom on the quinoline ring and the triazine ring together serve as multidentate coordination sites, directly and firmly "anchoring" zinc ions through coordination bonds, thereby inducing ZIF-8 to nucleate and grow uniformly and densely on the inner wall of silica gel.
[0052] The adsorption and separation material prepared by the above process combines the excellent mechanical strength, rigid framework and good macroscopic mass transfer channels of macroporous silica gel with the ultra-high specific surface area and rich microporous structure of MOF material, overcoming the problems of pure MOF powder being difficult to form and the weak interfacial bonding of traditional physical loading processes.
[0053] The modified silane coupling agent prepared in Comparative Example 2 lacks ether bonds, and the chemically inert long-chain alkyl group lacks ether oxygen atoms that can coordinate with zinc ions, which reduces its ability to induce the "anchoring site" for ZIF-8 to nucleate and grow in situ on the silica gel surface, resulting in a decrease in the effective loading capacity of MOF and its binding ability with the support.
[0054] Comparative Example 3 replaced the quinoline in the large conjugated system with a monocyclic imidazole, weakening the coordination-inducing ability of the modified silane coupling agent for zinc ions, resulting in reduced anchoring stability of ZIF-8 after in-situ growth compared to the examples. Simultaneously, the absence of the strong π-π interaction of quinoline reduced the affinity for aromatic pollutants such as toluene, ultimately decreasing both the breakthrough adsorption capacity and cycling stability of the material.
[0055] Although the initial adsorption capacity of Comparative Example 4 was acceptable, the Si-O-Si covalent network formed between the modified silane coupling agent and the support in this comparative example was relatively small, resulting in weak pyrolysis stability and anchoring ability. Therefore, after 20 cycles of thermal desorption at 150℃, the cycle retention rate decreased significantly.
[0056] Comparative Example 6 lacked the step of activating silica gel with dilute nitric acid. The untreated silica gel surface had fewer free silanol groups, resulting in limited covalent grafting ability of the modified silane coupling agent. The modified silane coupling agent and the support had difficulty forming a Si-O-Si covalent bond network, which in turn reduced the in-situ anchoring ability of the modified silane coupling agent to ZIF-8. Therefore, ZIF-8 and the modified silane coupling agent were more prone to peeling off during desorption cycles compared to the examples, and the performance of the separation material decreased.
[0057] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. However, any modifications, alterations, and variations made by those skilled in the art without departing from the scope of the present invention based on the disclosed technical content are equivalent embodiments of the present invention. Furthermore, any modifications, alterations, and variations made to the above embodiments based on the essential technology of the present invention are still within the protection scope of the present invention.
Claims
1. A method for preparing a silica gel composite adsorption and separation material, characterized in that, Includes the following steps: (1) Add macroporous silica gel to dilute nitric acid solution, heat and stir, wash with water until neutral, and then dry to obtain activated silica gel; (2) Disperse activated silica gel in anhydrous toluene, add modified silane coupling agent, stir to react, wash and dry to obtain modified silica gel; In step (2), the reaction is carried out under the protection of an inert gas, the reaction temperature is 90-100℃, and the reaction time is 12-24h; (3) The modified silica gel was immersed in zinc salt solution, 2-methylimidazole solution was added dropwise, and the reaction, filtration, washing and vacuum activation were carried out to obtain silica gel composite adsorption and separation material; In step (3), the vacuum activation temperature is 80-100℃ and the time is 12-24h; The structural formula of the modified silane coupling agent is as follows: 。 2. The method for preparing a silica gel composite adsorption and separation material according to claim 1, characterized in that, In step (1), 5-15 mL of dilute nitric acid solution is added to every 1 g of the macroporous silica gel.
3. The method for preparing a silica gel composite adsorption and separation material according to claim 1, characterized in that, In step (1), the heating and stirring treatment is carried out at a temperature of 80-100℃ for 4-8 hours.
4. The method for preparing a silica gel composite adsorption and separation material according to claim 1, characterized in that, In step (2), the mass ratio of activated silica gel to modified silane coupling agent is 1:(0.1-0.5).
5. The method for preparing a silica gel composite adsorption and separation material according to claim 1, characterized in that, In step (3), the zinc salt is zinc nitrate.
6. The method for preparing a silica gel composite adsorption and separation material according to claim 1, characterized in that, In step (3), the concentration of the zinc salt solution is 0.1-0.25 mol / L, and the solvent of the zinc salt solution is one of methanol and ethanol; the concentration of the 2-methylimidazole solution is 2.0-2.5 mol / L, and the solvent of the 2-methylimidazole solution is one of methanol and ethanol.
7. The method for preparing a silica gel composite adsorption and separation material according to claim 1, characterized in that, In step (3), 25-45 mL of the zinc salt solution and 5-10 mL of the 2-methylimidazole solution are added to 1 g of the modified silica gel.
8. A silica gel composite adsorption and separation material, characterized in that, It is prepared by the preparation method according to any one of claims 1-7.
Citation Information
Patent Citations
Novel silica gel compound adsorption and separation material and preparation method thereof
CN101804321A
Silica gel loaded polymeric amine and 8-hydroxyquinoline dual-function base compound adsorption material and preparation method
CN102671644A